COUPLED SUPPORT CONTRIBUTION TO REGIONAL DEVELOPMENT OF THE SHEEP AND GOAT SECTOR IN ROMANIA - Mariana GRODEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Coupled support is one of the main payment schemes from the “optional direct payments” category, introduced in the EU in the year 2015, funded by the Common Agricultural Policy from the European Agricultural Guarantee Fund (EAGF). At EU-28 level, in 2019, 73.2% of the total coupled support budget was directed to the livestock sector, out of which 12.6% to the sheep and goat farming sector. In the same year, the sheep and goat sector from Romania benefited from 64.3 million euros, as against 50.2 million euros in the year 2018, i.e. 37.1% of total livestock sector. The results obtained following this regional analysis reveal that the impact of this payment scheme implementation has positively impacted the development of the sector, both in terms of meat production, slaughtering in specialised units and livestock herds.